Insights Into Good University Governance In Indonesia: Do Internal Control And Whistleblowing Play A Role? - Anzib, Nuraini,; Mulyany, Ratna; Fitri, Fauziah Aida (Jurnal ASET (Akuntansi Riset), 2021)
This research is focused on evaluating the quality of internal control systems, the quality of good university governance and the model of developing good university governance through the application of whistleblowing. The population comprise of all individuals involved in the process of implementing good university governance and internal control units (SPI) that exist in 4 provincial public universities in Aceh, Indonesia, where sampling is done randomly at each level for university loyalists. The observation data were analyzed using multiple regression model through the quantitative approach. The results findings indicate that internal control plays an important role in strengthening good university governance, while whistleblowing has no effect on strengthening good university governance. It indicates that whistleblowing has not been effectively used as mechanism to support good university governance and generally practiced in informal form without proper structure and mechanism of whistleblowing in place